2013
DOI: 10.1073/pnas.1300131110
|View full text |Cite
|
Sign up to set email alerts
|

Node-by-node disassembly of a mutualistic interaction web driven by species introductions

Abstract: Interaction webs summarize the diverse interactions among species in communities. The addition or loss of particular species and the alteration of key interactions can lead to the disassembly of the entire interaction web, although the nontrophic effects of species loss on interaction webs are poorly understood. We took advantage of ongoing invasions by a suite of exotic species to examine their impact in terms of the disassembly of an interaction web in Patagonia, Argentina. We found that the reduction of one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 45 publications
0
65
0
Order By: Relevance
“…Previous studies highlight the importance of shifts in the density of plant resources in degraded habitats as determinants of the direction and magnitude of land-use effects on mutualistic plant-animal interactions 15,20,28,29 . Although pollinators and seed dispersers differ in their specialization on food plants 30 , both may respond similarly to changes in the densities of the plants 9,10,31 . Accordingly, path analyses revealed that shifts in plant population densities between old-growth forest and logged forest largely explained the magnitude of the effects of logging on interactions of plants with their pollinators and seed dispersers ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies highlight the importance of shifts in the density of plant resources in degraded habitats as determinants of the direction and magnitude of land-use effects on mutualistic plant-animal interactions 15,20,28,29 . Although pollinators and seed dispersers differ in their specialization on food plants 30 , both may respond similarly to changes in the densities of the plants 9,10,31 . Accordingly, path analyses revealed that shifts in plant population densities between old-growth forest and logged forest largely explained the magnitude of the effects of logging on interactions of plants with their pollinators and seed dispersers ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A key question is hence whether habitat degradation has correlated effects on multiple interaction networks each providing different ecosystem services, such as pollination and seed dispersal 4,7 . For example, a correlated response to habitat degradation could arise through the sharing of plant resources among different interaction networks [7][8][9] . Simulations suggest that extinction of plants can cause correlated co-extinctions in different interaction networks when these are coupled through shared plant resources 7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the effects of species losses on ecosystem processes has been explored mostly through community-level studies that assess relationships between biodiversity and ecosystem functioning (Cardinale et al 2012), often to the exclusion of other approaches (Wardle 2016). It stands to reason that, as gains and losses of species are occurring simultaneously, understanding how forests are responding to human-induced species changes requires joint consideration of the effects of both species gains and losses as well as the net effect of both processes (Rodriguez-Cabal et al 2013). Disentangling the ecosystem effects of species gains and losses is nontrivial.…”
Section: Simultaneous Gains and Losses Of Speciesmentioning
confidence: 99%
“…In general, the impacts of invasive species on native species are greatest when they introduce novel traits and become dominant members of a community. For example, alien herbivores can modify plant communities by directly affecting plant survival, growth and fitness through browsing, grazing and trampling (Crawley 1986, BarriosGarcia et al 2012 or through indirect effects by altering nutrient cycles, primary productivity, disturbance regimens, and disrupting mutualisms (Williamson 1996, Mack and D'Antonio 1998, Rodriguez-Cabal et al 2013). Yet, it remains unclear whether alien herbivores are introducing novel traits and are, therefore, functionally different than native herbivores or whether alien herbivores are performing similarly to native herbivores, but simply have higher abundances.…”
Section: Introductionmentioning
confidence: 99%